Ocular Manifestations in HIV/AIDS Patients Undergoing Highly Active Antiretroviral Therapy - Oudah Alghamdi, Durraiz Rehman, Muhammad Abdul Rehman Akram, Mazen Ahmed Alzahrani, Asim Mahmood, Thamer Basodan (Pakistan Journal of Ophthalmology, 2019)
Purpose: To study Human Immunodeficiency Virus (HIV) / Acquired Immunodeficiency Syndrome (AIDS) related ocular manifestations in patients undergoing highly active anti-retroviral therapy (HAART) in Jeddah, Saudi Arabia. Study Design: Descriptive study. Place and Duration of Study: Ophthalmology Clinic of East Jeddah Hospital. Kingdom of Saudi Arabia, during 2016-2017. Material and Methods: All patients who were positive for HIV/AIDS and taking highly active anti-retroviral therapy seen in the department of Infectious diseases of our hospital were included in the study. The data for the 47 HIV/AIDS positive referrals was collected from the Infectious Diseases Department by taking history, clinical examinations, and laboratory investigations. The ophthalmological examination consisted of adnexal examination, best corrected visual acuity, Intraocular pressure (IOP), anterior and posterior segment examination, B-scan and MRI. Results: There were 47 patients included in the study. There was one patient each of retinal necrosis, anterior uveitis ?and? neovascular glaucoma, pterygium, sixth nerve palsy, bacterial conjunctivitis and adenoviral conjunctivitis. Two cases presented with HIV microangiopathy, blepharitis, cortical blindness after brain abscess, herpes infection, Kaposi sarcoma and cytomegalovirus (CMV) retinitis. Three patients presented with meningitis and six with dry eyes. Eight patients presented with cataracts and ten with refractive errors tuberculosis. Conclusion: Ocular manifestations of HIV infection are relatively infrequent in patients on HAART as this has reduced the HIV-related complications in ophthalmology. Keywords: Human Immunodeficiency Virus, Acquired Immunodeficiency Syndrome, Highly Active Anti-Retroviral Therapy.